2018
DOI: 10.31018/jans.v10i3.1717
|View full text |Cite
|
Sign up to set email alerts
|

Intra-specific morphological and morphometric variability of Radopholus similis (Cobb, 1893) Thorne, 1949

Abstract: Abstract:All the root inhabiting migratory endoparasitic nematode populations of Radopholus procured from banana crop of Vellayani, Thiruvananthapuram, Kerala were identified as Radopholus similis. Heat killed females were straight to slightly ventrally curved posteriorly. Female's head was low, rounded, continuous or slightly setoff with the body contour.Females were 500-660 µm long and were comparatively longer than males. Males had button shaped head set off by a constriction; female with three to five lip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
3
1
0
Order By: Relevance
“…Identification and characterization of R. similis showed that this nematode species was present in banana crops in all agro-ecological zones included in this study, making it a potential threat to banana production in Tanzania. Morphological and morphometric characterization of R. similis generally concurred with descriptions and measurements reported in other studies ( Ryss and Wouts, 1992 ; Elbadri et al, 1999 ; Murukesan et al, 2005 ; Roy et al., 2018 ). Most R. similis specimens from Zanzibar had greater total body length than those from the mainland.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Identification and characterization of R. similis showed that this nematode species was present in banana crops in all agro-ecological zones included in this study, making it a potential threat to banana production in Tanzania. Morphological and morphometric characterization of R. similis generally concurred with descriptions and measurements reported in other studies ( Ryss and Wouts, 1992 ; Elbadri et al, 1999 ; Murukesan et al, 2005 ; Roy et al., 2018 ). Most R. similis specimens from Zanzibar had greater total body length than those from the mainland.…”
Section: Discussionsupporting
confidence: 88%
“…However, we found that male and female stylet lengths fell outside of standard diagnostic values ( Ryss and Wouts, 1992 ; Elbadri et al, 1999 ), possibly due to variations in environmental conditions that drive morphological adaptation. We also found that males had slender bodies compared to females and degenerated stylets in all zones, reflecting the lower level of damage that males inflict as reported by Ryss and Wouts (1992) and Roy et al (2018) .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The nematode Radopholus similis recovered from this study showed morphological similarities as reported in India [15]. The body position of the female R. similis is straight, and the tail is slightly curved when during the fixation.…”
Section: Morphological Characters Of Phytonematodes In Ginger Cultiva...supporting
confidence: 74%
“…Según Ryss (2003), en nematodos pertenecientes a la familia Pratylenchidae, el valor del carácter alométrico b se incrementa durante el crecimiento postembrionario, debido a la elongación del cuerpo. En este sentido, Roy et al (2018) encontraron variabilidad en el carácter alométrico b en diferentes poblaciones de R. similis de la India, lo cual contrasta con los altos valores en estos caracteres para la población de Carepa, posiblemente debido a las condiciones específicas de ambiente y hospedante en esta región; los cuales pueden influir en el fenotipo resultante para esta población.…”
Section: Análisis De Componentes Principales (Acp) Y Conglomerados Je...unclassified